Peredaman Radikal Bebas Ekstrak Etanol Daun Rosella (Hibiscus sabdariffa L) Dengan Metode Frap (Ferric Reducing Antioxidant Power) - Vina Farah Fauziah; Devika Nurhasanah; Nofran Putra Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2023)
Background: Antioxidant are chemical compounds that can donate electrons to unpaired free radicals, thereby reducing the effects of free radical oxidation. One of the plants that have antioxidants activity is the rosella plant, for example in the leaves. Rosella leaves contain phytochemical compounds that are useful as antioxidant, namely flavonoids, alkaloids, saponins, tanin.Objective: Determine the antioxidant activity of the ethanol extract of rosella leave (Hibiscus sabdariffa L) by FRAP method.Method: Rosella leaf was macerated using 70% ethanol as solvent. Then filtered and thicken using a frying pan on an electric stove over medium heat of approximately 300 watt. Phytochemical screening was carried out, namely flavonoids, alkaloids, saponins, tanin and TLC test to indicate the presence of flavonoid compounds as antioxidants. Quantitative analysis was carried out to determine antioxidant activity with the FRAP method measured using a UV-Vis spectrophotometer.Result: The antioxidant activity test of the ethanol extract of rosella leaves has FRAP value of 1,749 mmol FeSO4/mg. Based on statistical analysis T-test, shows that there is a difference between the sample and the standard with a significant value (p<0,05) is 0,001.Conclusion: The antioxidant activity test on rosella leaves with the FRAP method proved that the ethanol extract of rosella leaves had antioxidant content with a FRAP value of 1,749 mmol FeSO4/mg.